Newspapers' portrayal of mass actions staged by protest groups - Javier, Abigail Ralativo 1977-
A truly meaningful education today is not confined to learning theories within the four walls of the classroom. The environment within and outside the school plays a pivotal role in shaping minds which can be analytical and critical so that people may be able to respond correctly to the everchanging social, political and economic issues surrounding them. Thus, the researcher decided to undertake a study on a subject which is outside the realm of the classroom: an analysis of the portrayal by two leading national newspapers, namely the Philippine Daily Inquirer and the Philippine Star, of the mass actions of the two major protest groups, the Kilusang Mayo Uno (KMU) and the League of Filipino Students (LFS). This study has a three-fold purpose: to arouse interest, to criticize and to encourage people to be involved in taking positive actions on specific issues affecting our social, political, and economic life. Two groups of respondents were purposively chosen. The first group was composed of UP students. They were chosen because exposure to protest actions as well as to the print media constitutes education outside the classroom. Besides, UP students are known for their ability to plunge into discussions of meaningful issues within the social, political and economic spectrum. The second group, on the other hand, was composed of members of the KMU and the LFS. They were chosen primarily because of their actual exposure or "inside" knowledge acquired through their actual participation in mass actions. This study used the survey method, focused interviews and content analysis. It sought to determine how the Philippine Daily Inquirer and the Philippine Star portrayed the mass actions staged by the two protest groups, the KMU and the LFS. It also sought to determine the perceptions of the UP students and members of protest groups of the way the two newspapers portrayed the mass actions in their news articles. The study revealed many interesting findings. A tally of the answers of the one hundred (100) respondents purposively selected indicated that UP students had a neutral stand on the manner the two newspapers, the Philippine Daily Inquirer and the Philippine Star wrote about the mass actions of KMU and LFS. However, the survey showed that the UP students perceived that the newspapers tended to favor a little bit the LFS over the KMU. The results of the focused interviews indicated that majority of the KMU were of the agreement that the news articles on the mass actions of the protest groups were more on the positive side. On the other hand, the members of the LFS were divided on their perception. The content analysis part of the study revealed that the news articles of the Philippine Daily Inquirer and the Philippine Star had both positive and negative portrayal of the mass actions of the KMU and the LFS. However, the study indicated that although a big majority of UP students were daily readers of the Philippine Daily Inquirer and the Philippine Star, they seemed unconcerned about news articles pertaining to the mass actions of the KMU and the LFS. They were not certain if the portrayal of the newspapers towards the mass actions of these protest groups were positive or negative. The KMU and the LFS members on the other hand, were of the general perception that the newspapers positively portrayed the mass actions of their protest groups. The content analysis showed that frequently, the mass actions of the KMU and the LFS were both positively and negatively portrayed by the Philippine Daily Inquirer and the Philippine Star in their news articles. The findings also revealed that factors such as the students' individual or personal perception, their involvement in the mass actions of the KMU and the LFS, as well as their interaction with members of the KMU and the LFS members could have affected albeit, minimally, their perception of the way the two leading newspapers portrayed the mass actions of the two protest groups. The researcher recommends that a more comprehensive questionnaire be designed in order to discourage the tendency of the respondents to opt for a 'neutral' answer. The respondents and informants likewise should be habitual newspaper readers so that hey could be effective and reliable subjects for the study. The researcher also recommended that with regard to the content analysis part, the number of news articles about the protest groups be increased to enable a future researcher to cover greater ground. The time period allotted for the gathering of news articles pertaining to mass actions should also be longer because one has to contend with the fact that protests are hel as issues arise.